A Direct CH/ArH Coupling Approach to Oxindoles, Thio‐oxindoles, 3, 4‐Dihydro‐1 H‐quinolin‐2‐ones, and 1, 2, 3, 4‐Tetrahydroquinolines. Issue 43 (11th September 2014) - Hurst, Timothy E.; Gorman, Ryan M.; Drouhin, Pauline; Perry, Alexis; Taylor, Richard J. K.
Abstract A copper(II)‐catalysed approach to oxindoles, thio‐oxindoles, 3, 4‐dihydro‐1H‐quinolin‐2‐ones, and 1, 2, 3, 4‐tetrahydroquinolines via formal CH, ArH coupling is described. In a new variant, copper(II) 2‐ethylhexanoate has been identified as an inexpensive and efficient catalyst for this transformation, which utilises atmospheric oxygen as the re‐oxidant.